Inverse association of insulin antibody levels with insulin sensitivity in adults with Type 1 diabetes. Issue 5 (24th March 2018) - Burkart, V.; Strassburger, K.; Zivehe, F.; Markgraf, D.; Herder, C.; Müssig, K.; Szendroedi, J.; Schloot, N.; Roden, M.; ,
Abstract: Aims: Insulin resistance may contribute to the pathogenesis of autoimmune‐mediated diabetes. Antibodies against β‐cell‐associated molecules, comprising islet cell antigen (ICA), glutamic acid decarboxylase (GAD) and insulin, characterize the autoimmune process. Because the link between insulin resistance and autoimmunity might be relevant for disease progression and treatment, we hypothesized that insulin resistance associates positively with β‐cell‐directed antibodies in newly diagnosed Type 1 diabetes. Methods: Within the German Diabetes Study, an observational study including adults with newly diagnosed diabetes, 142 adults [84 men, 58 women; age 33.1 (26.4, 41.9) years; diabetes duration 6.3 (4.2, 9.1) months] positive for at least one antibody against ICA, GAD or insulin underwent hyperinsulinaemic–euglycaemic clamp tests to assess insulin sensitivity (M‐value) in a cross‐sectional setting. Results: Insulin‐directed antibodies were inversely correlated with M‐values (β = −0.039). Albeit not strong, the association persisted after adjustment for age, sex and BMI, and even after further adjustment for confounders reflecting exposure to exogenous insulin and residual β‐cell secretory capacity. Correlation network‐based analyses revealed a complex interaction between levels of fasting insulin and of insulin antibodies with respect to their relationship with the M‐value. GAD‐ or ICA‐directed antibodies did not correlate with insulin sensitivity. Conclusions: In adults with recent‐onset Type 1 diabetes expressing at least one β‐cell‐directed antibody, insulin sensitivity is inversely related to insulin antibody titres, but not to other autoantibodies. Our finding may allow for the identification of insulin resistance in adults with high levels of insulin antibodies. What's new?: In adults with recent‐onset Type 1 diabetes, insulin antibody levels are inversely associated with insulin sensitivity. Levels of antibodies against glutamic acid decarboxylase or islet cell antigen do not correlate with insulin sensitivity.